2010
DOI: 10.1115/1.4002886
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Effect on a Cavitating Inducer in Liquid Hydrogen

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Such a model was justified by some previous investigators in the studies of both conventional hydraulic machines [13,52], and cryogenic turbomachines [7][8][9], with the cavitation models having been verified by the prese t team of authors in our previous publications [42,44]. The cryogenic hydrofoil flow was simulated and the predicted surface static pressure and temperature were consistent with the test data [53] (Figure 3).…”
Section: Of 21mentioning
confidence: 61%
See 2 more Smart Citations
“…Such a model was justified by some previous investigators in the studies of both conventional hydraulic machines [13,52], and cryogenic turbomachines [7][8][9], with the cavitation models having been verified by the prese t team of authors in our previous publications [42,44]. The cryogenic hydrofoil flow was simulated and the predicted surface static pressure and temperature were consistent with the test data [53] (Figure 3).…”
Section: Of 21mentioning
confidence: 61%
“…Similar to conventional hydraulic turbomachines of pumps and hydraulic turbines, detrimental cavitation also unavoidably occurs in liquid turbine expanders. Cavitation of conventional hydraulic turbomachines has attracted considerable research, but very limited work on cryogenic turbomachines has been reported [7][8][9].In both conventional hydraulic turbines and pumps, swirling-flow-induced cavitation is significant and detrimental [10][11][12][13][14][15]. In hydraulic turbines, swirling flow originates from the rotating impeller, but further propagates downstream into the diffuser tube, leading to considerable mechanical head dissipations [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the simulation of a cavitating flow through a venturi, [1] proposed a sinus barotropic law considering a direct link between the gas volume fraction, phasic densities, local pressure and vapour saturation pressure. For the simulation of cavitating flows in tubopump inducers of spatial rockets, [6] proposed a sinus barotropic law with a vapour saturation pressure calculated from local temperature in the flow. Those robust approaches have provided interesting results for the simulation of hydrofoils [7], venturies [8], turbopump inducers [9,10,11], pumpturbines [12] or fuel injectors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have attempted to take into account the effect of liquid phase thermal gradients in the flow on cavitation. For barotropic approach [34,6] as well as for inertial controlled growth model [33,35,36], it has been done meanly by calculating the saturated vapour pressure as a function of the local temperature (p sat (T )) and by estimating the bubble temperature variation using energy balance at the bubble scale. In the same time, a few numerical works evoked that vapour production can be driven by thermal controlled growth of vapour bubbles [37,38,39,5].…”
Section: Introductionmentioning
confidence: 99%